All Days 2008
DOI: 10.2523/iptc-12390-ms
|View full text |Cite
|
Sign up to set email alerts
|

Temana Field Pilot Implementation : A Shift In Sand Control Philosophy To Improve Well Performance

Abstract: The Temana field consists of unconsolidated reservoirs which require active sand control. Conventional Internal Gravel Packed (IGP) technique has been widely applied as it has provided a reliable means of abating sand production. These completions however, have shown high skins (>15) which had increase with time due to fines migration into the packed area especially with the advent of water production. In many cases, flow efficiencies were reduced by 70% and this had severely affected well performances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Such as, Tiffin (Tiffin et al 1998(Tiffin et al , 2003 introduced two new parameters in sand control with the sand particle size distribution: sorting characteristics (SC = d10/d95) and fine particles (the quality percentage of \45 lm particles), and the gravel packing completion was used in the formation of high fine particles content. Mohamad et al (2008) published an article in the JPT which showed fine particles (\45 lm) content with 35 %. The gravel packing was used in the initial stage, and it found that the skin was very high under this way.…”
Section: Introductionmentioning
confidence: 99%
“…Such as, Tiffin (Tiffin et al 1998(Tiffin et al , 2003 introduced two new parameters in sand control with the sand particle size distribution: sorting characteristics (SC = d10/d95) and fine particles (the quality percentage of \45 lm particles), and the gravel packing completion was used in the formation of high fine particles content. Mohamad et al (2008) published an article in the JPT which showed fine particles (\45 lm) content with 35 %. The gravel packing was used in the initial stage, and it found that the skin was very high under this way.…”
Section: Introductionmentioning
confidence: 99%